Diagnosis Protocol of Stomach Distemperament for Clinical Practice in Iranian Traditional Medicine: A Narrative Review - Mahdi ALIZADEH; Ebrahim KHADEM; Jale ALIASL (Tehran University of Medical Sciences, 2017)
Background: In Iranian traditional medicine (ITM) stomach is the important organ in the body. Its disorders can affect other organs such as liver, heart and also can cause depression. Stomach distemperaments can cause some disorders. Thepurpose of this study was to provide a diagnostic method of stomach distemperament for clinical practice. Methods: In this study authoritative ITM books such as Canon of Avicenna, Zakhirah-E-Kharazm Shahi by Hakim Esmail Jorjani, Kamel al -Sina'ah al- Tibbiyah by Ali ibn al-'Abbas al-Majusi were assessed and symptoms and signs of stomachdistemperament were collected. Results: Stomach has some normal temperament. The imbalance in temperament and humor can cause distemperments. There are 12 types of stomach distemperament and based on symptoms and signs a primary protocol is designed for diagnosis of stomach distemperament. Conclusion: There is no available guideline for gastric distemperamet diagnosis protocol. As a result, the presented protocol should be considered for use in clinical practice.